Organized violence after civil war: the geography of recruitment in Latin America - Daly, Sarah (Cambridge studies in comparative politics, 2016)
"Nearly half of all countries emerging from conflict relapse into war within a few years of signing a peace agreement. The post-war trajectories of armed groups vary from demilitarization to remilitarisation. In Organized Violence after Civil War, Daly analyzes evidence from 37 militia groups in Colombia, demonstrating that the primary driving force behind these changes is the variation in recruitment patterns within, and between, the warring groups after peace accords. She documents the transition from war to peace in interviews with militia commanders, combatants and victims. Using rich ex-combatant survey data and geo-coded information on violence over forty years of war, Daly explains the dynamics inside armed organizations and the strategic interactions between them. She also shows how these theories can be used beyond Colombia, both within the region of Latin America and in the rest of the world"--